Criminological classification of robots: risk-based approach - I. R. Begishev (Правоприменение)
The subject of the research is key criminal risks in robotics. The purpose of the article is to confirm or disprove the hypothesis that key criminal risks of using robots may be identified and classified. The author dares to describe the key aspects of the application of risk-based approach in the assessment of robotic activities, identify the key risks of using robots, give a criminological classification. The methodology includes a formal logical method, systematic approach, formal legal interpretation of legal acts and academic literature, SWOT analysis. The main results of the study. The author applies the main provisions of criminal riskology when assessing encroachments involving robots. Key risks and challenges when using robots are identified. The severity of the consequences of harm caused by using robots (from minor to critical risk) is assessed and a matrix of the probability of its occurrence is provided. The author's criminological classification of robots is based on the risk-based approach and is substantiated on two grounds. The first one is the category of public danger and the second is the potential severity of the consequences of harm caused by robots. The causal complex that can lead to criminal risks in robotics is identified. The grounds of such risks are divided into those related to the mechanical subsystem of robots, digital subsystem of robots and power supply subsystem of robots. Conclusions. The risk-based approach is the most progressive and effective basis for regulating the criminal relations in robotics. The author demonstrates the existence of real risks to the peace and security of mankind, life and health of people, objects of wildlife, nonliving material objects from the use of robots. It is necessary to recognize robotics as source of increased potential criminal danger and to adopt appropriate regulation as soon as possible. The necessity and expediency of applying a risk-based approach to robotics is theoretically substantiated, and the characteristics of robots that are important in assessing the criminal potential of their exploitation are evaluated. The conclusions and recom mendations of this paper may become a basis for the implementation of the risk-based approach in legal regulation of robotics. The risk matrix presented in the article can be used to establish a framework for regulatory impact on robotics, assess the consequences of potential harm and minimize it.